Regional malaria and ther communicable disease threats trust fund final report. (Asian Development Bank, 2018)
This report details the key achievements of the Regional Malaria and Other Communicable Disease Threats Trust Fund from its creation in 2013 to the first half of 2018. It provides detailed analysis of the results by outcome, profiles specific projects that serve as exemplars of the fund impact, and offers insights into how similar trust funds can be managed for success in future.